2017
DOI: 10.1017/s1041610217002563
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent benzodiazepine use in older adults treated with antidepressants in Asia

Abstract: Nearly, half of the older adults treated with antidepressants in Asia are prescribed concurrent benzodiazepines. Given the potentially adverse effects of benzodiazepines, the rationale of benzodiazepines and antidepressants co-prescription needs to be revisited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Our study showed that 54.9% (before PS matching) of adults with incident depression received AD+BZD therapy, which was comparable to those (40-50%) in previous studies on other Asian [31,32] or Caucasian populations [33]. While the clinical manifestation of depression in Korean patients could have been different from that of patients of other countries, cultures, or ethnicities [34], we found similar proportions of AD+BZD use among patients with depression.…”
Section: Discussionsupporting
confidence: 83%
“…Our study showed that 54.9% (before PS matching) of adults with incident depression received AD+BZD therapy, which was comparable to those (40-50%) in previous studies on other Asian [31,32] or Caucasian populations [33]. While the clinical manifestation of depression in Korean patients could have been different from that of patients of other countries, cultures, or ethnicities [34], we found similar proportions of AD+BZD use among patients with depression.…”
Section: Discussionsupporting
confidence: 83%
“…Other research foci include psychiatric management patterns (Abdul Khaiyom, Mukhtar, & Oei, 2019; Dong et al, 2019; S.‐C. Park, Oh, et al, 2019; Zhong et al, 2019), electroconvulsive therapy, validations of translated scales (C.‐S. Ang, 2020; Cheung, Yeo, Chong, Khoo, & Wee, 2019; Din et al, 2019; Khairani, Ahmad, Ismail, & Aman, 2020; N. T. P. Pang, Kamu, et al, 2020), stigma (Ibrahim, Amit, et al, 2019; Sun et al, 2019) and child and adolescent psychiatry (Adib et al, 2019a, 2019b; A. L. Ang, Wahab, Abd Rahman, Hazmi, & Md Yusoff, 2019; Chhoa et al, 2019; Ibrahim, Amit, et al, 2019; Ibrahim, Che Din, et al, 2019; Ramachandram, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The Research on Asian Psychotropic Prescription Patterns for Antidepressants (REAP‐AD) project is an international, multicentre survey on the use of ADs, which was conducted between March and June 2013 in 42 centres and hospitals in 10 Asian territories and countries, including China, Malaysia, Hong Kong, India, Indonesia, Japan, Thailand, Korea, Singapore and Taiwan. Patients with any mental disorder treated with ADs on the day of data collection were consecutively screened and enrolled in the survey.…”
Section: Methodsmentioning
confidence: 99%